2007
DOI: 10.1111/j.1468-3148.2007.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Costs of Residential Services for Adults with Intellectual Disabilities in Taiwan: A Comparative Evaluation

Abstract: Background The disability policy in Taiwan has traditionally emphasized residential care in large institutions and, more recently, medium-sized group homes. This paper compares the relative costs, services provided and outcomes between the traditional institutions, mediumsized group homes and new small-scale community living units that were launched in 2004 in Taiwan. Materials and Methods Cross-sectional analysis was used to investigate the three current residential service models. A total of 248 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 25 publications
4
36
0
3
Order By: Relevance
“…There are a number of implications from this finding. First, this suggests (as found in previous studies; Chou et al . 2008) that the choices available in ‘where to live’ and ‘who to live with’ were not made by the residents.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There are a number of implications from this finding. First, this suggests (as found in previous studies; Chou et al . 2008) that the choices available in ‘where to live’ and ‘who to live with’ were not made by the residents.…”
Section: Discussionsupporting
confidence: 82%
“…As described previously, small ordinary residential models like this new scheme have just started in Taiwan. In Chou et al . 's (2008) study, consistent with Western studies, the evaluation of this community‐based new residential scheme for adults with IDs has shown that it is the most cost‐effective choice when compared to institutional care, but the service structure in Taiwan is still dominated by institutional care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is definitely a major limitation in this study. Moreover, as noted in both Power (2008) and Chou et al . (2008), Western countries strongly favour the deinstitutionalisation of adults with ID, where the provision of support to live in their own homes within the community has become a mainstream policy.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, people with intellectual disability living in small residential homes experienced better outcomes at lower cost than persons living in medium-sized group homes or institutions [33]. In addition, staff working at small homes had a significantly higher level of job satisfaction than staff in other types of institutions; the characteristics of the residential setting are thus factors of concern when ensuring staff job satisfaction [34 ].…”
Section: Social Policy For People With Intellectual Disabilitymentioning
confidence: 99%